The Response of the Village Community to the Government's Policy in Performing Worship During the Covid-19 Pandemic - Khikam, A Bahrul (Sultan Journal of Social Sciences and Humanities, 2024)
This research intends to describe the attitude of the community in the village of Tanggungprigel in terms of worship activities. This worship activity was carried out in accordance with the direction of the village government in order to inhibit and break the Covid-19 chain. The condition of the community when carrying out worship activities is currently very depressed. One of them is the worship that is carried out by Muslims in the village of Tanggungprigel, Glagah District, Lamongan Regency. During this pandemic the government issued a policy in terms of performing worship. In this study, researchers used quantitative methods. The purpose of using quantitative methods is to collect specific phenomena. There are still many Muslims who cannot leave their habits when carrying out worship activities such as congregational prayers, congregational tarawih prayers, Eid prayers and recitations such as tahlilan, manaqiban, dibaan including in the village of Tanggungprigel. This phenomenon is the object of this study. The results of the study found that the religious activities of the Wargaprigel village during the covid-19 pandemic experienced many changes, initially activities that were public. Now it tends to be quiet and closed. At a deeper level, there is a unique pattern that involves four variables, namely the level of worship, the level of participation, social distancing recommendations, and the attitude of the Wargaprigel village community in implementing local village government policies.